Worldwide incidence of aneurysmal subarachnoid hemorrhage according to region, time period, blood pressure, and smoking prevalence in the population: a systematic review and meta-analysis - Etminan, Nima; Chang, Han-Sol; Hackenberg, Katharina (JAMA neurology, 2019)
Importance Subarachnoid hemorrhage (SAH) from ruptured intracranial aneurysms is a subset of stroke with high fatality and morbidity. Better understanding of a change in incidence over time and of factors associated with this change could facilitate primary prevention. Objective To assess worldwide SAH incidence according to region, age, sex, time period, blood pressure, and smoking prevalence. Data Sources We searched PubMed, Web of Science, and Embase for studies on SAH incidence published between January 1960 and March 2017. Worldwide blood pressure and smoking prevalence data were extracted from the Noncommunicable Disease Risk Factor and Global Burden of Disease data sets. Study Selection Population-based studies with prospective designs representative of the entire study population according to predefined criteria. Data Extraction and Synthesis Two reviewers independently extracted data according to PRISMA guidelines. Incidence of SAH was calculated per 100 000 person-years, and risk ratios (RRs) including 95% CIs were calculated with multivariable random-effects binomial regression. The association of SAH incidence with blood pressure and smoking prevalence was assessed with linear regression. Main Outcomes and Measures Incidence of SAH. Results A total of 75 studies from 32 countries were included. These studies comprised 8176 patients with SAH were studied over 67 746 051 person-years. Overall crude SAH incidence across all midyears was 7.9 (95% CI, 6.9-9.0) per 100 000 person-years; the RR for women was 1.3 (95% CI, 0.98-1.7). Compared with men aged 45 to 54 years, the RR in Japanese women older than 75 years was 2.5 (95% CI, 1.8-3.4) and in European women older than 75 years was 1.5 (95% CI, 0.9-2.5). Global SAH incidence declined from 10.2 (95% CI, 8.4-12.5) per 100 000 person-years in 1980 to 6.1 (95% CI, 4.9-7.5) in 2010 or by 1.7% (95% CI, 0.6-2.8) annually between 1955 and 2014. Incidence of SAH declined between 1980 and 2010 by 40.6% in Europe, 46.2% in Asia, and 14.0% in North America and increased by 59.1% in Japan. The global SAH incidence declined with every millimeter of mercury decrease in systolic blood pressure by 7.1% (95% CI, 5.8-8.4) and with every percentage decrease in smoking prevalence by 2.4% (95% CI, 1.6-3.3). Conclusions and Relevance Worldwide SAH incidence and its decline show large regional differences and parallel the decrease in blood pressure and smoking prevalence. Understanding determinants for regional differences and further reducing blood pressure and smoking prevalence may yield a diminished SAH burden.